THE INFLUENCE OF COMBINED APPLICATION OF EXTRACTS OF HYPERICUM PERFORATUM AND GLYCYRRHIZA GLABRA ON THE DEVELOPMENT OF GASTROPATHY IN RATS - Mamadaliyev Sherzod Iminjon o‘g‘li; Egamberdiyev Jasur Jumanazar o‘g‘li (European Science Publishing, 2025)
The experiments were conducted on 24 male white rats weighing 180–200 g, in accordance with the requirements of the ethical committee. Two variants of gastropathy were modeled: stress-induced gastric ulcers caused by immobilization and ulcer formation induced by the administration of indomethacin. Rats in the experimental groups were orally administered Lesbokhol in the form of a dry extract intragastrically at a dose of 50 mg/kg one hour prior to the modeling of experimental ulcers. The results showed that under conditions of immobilization stress and indomethacin administration, multiple hemorrhages with pinpoint and linear ulcerations were observed in all test rats. However, with the administration of a combination of extracts from medicinal plants (Hypericum perforatum and Glycyrrhiza glabra), there was a significant reduction in both the number of rats with ulcers and the number of ulcers per rat.
Keywords: Hypericum perforatum, Glycyrrhiza glabra, gastropathy, gastric ulcers, stress-induced ulcers, indomethacin-induced ulcers, anti-ulcer effects, Helicobacter pylori (H. pylori).